Economic evaluation of biomass pyrolysis liquefaction technology based on life cycle assessment - JIN Mengyu; SONG Yuanbo; GU Minyan; SI Huiping; SHEN Zheng*; ZHANG Yalei (能源环境保护)
In the context of the "dual carbon" goals, exploring the production of bio-gasoline and bio-diesel through a biomass energy and pyrolysis liquefaction production chain holds significant potential. This approach could help alleviate China′s dependence on crude oil imports. Based on the construction of a bio-oil plant and its operational lifespan, the static investment payback period is 5.46 years, the dynamic investment payback period is 7.45 years, and the internal rate of return is 17%. The cumulative net present value is 20.21491 million yuan. To ensure profitability, the selling price of bio-diesel should not be lower than 6105.81 yuan per ton (assuming consistent production costs, production capacity, and sales capacity). The project is less sensitive to raw material prices than electricity costs, but requires a production scale greater than 1700 tons for profitability. Bio-oil plants should prioritize reducing energy consumption. An affordable and reliable raw material supply is crucial for the survival, development, and competitiveness of enterprises.